Strategic Management Of Narcotics Handling In The National Narcotics Agency Of Palu City - Risma Ariyani; M.Kafrawi Al- Kafiah Samsu; Yulizar Pramukida Tawil; Andi Maman Firmansyah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
The term Narcotics is familiar to the public, currently the abuse of narcotics, psychotropic and addictive substances (NARKOBA) is a very big problem, the development of scientific and technological progress in reality not only creates convenience in human life but also creates various problems, one of the major problems caused is the problem of narcotics, in Indonesia itself has been declared a drug emergency country because Indonesia is a country consisting of several islands that are very strategic for conducting drug trafficking transactions, to the high number of dealers in Indonesia, one of which is influenced by the ease of obtaining precursor raw materials for drug makers within the scope of self-managed home industries used by families from urban residents as an alternative livelihood, this issue is certainly a serious problem that can ultimately lead to disruption, security of national order, unrest and national losses.